How anthropomorphism is changing the social context of modern wildlife conservation - Manfredo, Michael J.; Urquiza-Haas, Esmeralda G.; Don Carlos, Andrew W.; Bruskotter, Jeremy T.; Dietsch, Alia M. (Biological conservation, 2020)
•The study reports results from a sample of 43,949 respondents from all 50 U.S. states.•Anthropomorphism is strongly associated with mutualist as opposed to domination wildlife values.•Modernization was weakly related to anthropomorphism at the individual level but was moderate at the state level.•Anthropomorphism leads to values not aligned with the ethics of traditional wildlife management. This study proposes that anthropomorphism is a key factor in stimulating both wildlife value shift and changing attitudes toward wildlife management in modernized countries. Evidence suggests that cultural shift due to modernization increases anthropomorphic attributions which leads to seeing wildlife as more human-like. This provides a foundation for a shift in values from domination, in which wildlife are for human uses, to mutualism in which wildlife are seen as part of one’s social community. This theoretical proposition was tested with a nationwide study of 43,949 U.S. subjects obtained by mail survey and e-mail panel. Values and anthropomorphism were measured using established item scaling. We found that, as expected, anthropomorphism is strongly related to mutualist values. It was weakly associated with modernization variables (income, urbanization, education) at the individual level and moderately associated at the state level. Results suggest a modernized environment fosters anthropomorphic attribution, but the variables we used are not the proximate cause of this process at individual level. To provide a partial test of the likely causal sequence, we found that the effect of anthropomorphism on attitudes is mediated by wildlife values. Anthropomorphism, through its effect in stimulating value shift, leads to challenges of traditional approaches to wildlife management. It emphasizes consideration of individual animals and the avoidance of lethal control techniques such as is proposed in the concept of compassionate conservation. Further research in other modernized countries with similar cultural characteristics is needed to establish the broader generalizability of our findings.